THE ROLE OF ARTIFICIAL INTELLIGENCE IN FOSTERING WOMEN'S GROWTH AND LEADERSHIP IN THE MODERN WORLD - Ebrahimi, Marzia; Hadadd, Zahra Hussaini; Ghory, Rabia; Yari, Tamana Ali; Ahmadi, Lima; Quraishi, Tamanna (International Journal of Multidisciplinary Research and Literature, 2025)
Artificial intelligence (AI) is increasingly recognized as a transformative tool capable of fostering women’s growth and leadership across various sectors. However, disparities in access, digital literacy, and socio-cultural barriers challenge the equitable benefits of AI for women worldwide. This study aims to explore the perceptions of women regarding AI’s potential to enhance leadership opportunities and identify key obstacles hindering its inclusive use. A mixed-methods survey was conducted with women participants from diverse backgrounds, focusing on their confidence in AI’s ability to empower leadership, as well as perceived barriers to AI adoption. Quantitative data were collected through structured questionnaires, while qualitative insights were gathered via open-ended responses to provide context to the challenges faced. Results indicate that 45% of respondents strongly believe AI can improve women’s leadership opportunities, with an additional 40% agreeing contingent upon adequate support. Major barriers identified include lack of digital literacy (35%), cultural and societal restrictions (30%), and limited access to technology (25%). Notably, only 10% cited algorithmic bias as a significant concern, highlighting a potential gap in awareness. These findings emphasize the need for targeted interventions addressing digital skills training, infrastructure development, and socio-cultural norms. In conclusion, while AI holds substantial promise as an enabler of women’s empowerment, its full potential can only be realized through integrated strategies encompassing education, technology access, ethical AI design, and cultural change. Policymakers, educators, and technologists must collaborate to foster an inclusive AI ecosystem that supports sustainable gender equity and leadership development.